Placenta humanum - Timmerman, Alize; Hair, Angela (Homœopathic Links, 2013)
This article centres on the proving of Placenta humanum by the Trituration method and the treatment of patients with the remedy derived from this trituration process. To illustrate the healing power of the triturated Placenta remedy, a number of cases are presented, one with a considerable number of follow-ups. The placenta is a crucial organ in the propagation of the species. The sarcode made from the placenta substance should be considered in all cases where lack of connection from roots and source are dominant symptoms. Also in cases where one cannot properly handle oneʼs own impulses, resulting in anxiety and restlessness, Placenta humanum may be the fitting remedy.
Keywords: Placenta humanum; Sarcodes; Disconnection from roots; Trituration